Indonesian Diplomacy in Resolving the Southern Thailand Conflict in Maintaining Regional Security Stability - Rahma Agun Aulal Muna; Abdul Rivai Ras; Rudiyanto Rudiyanto; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno (CV. AFDIFAL MAJU BERKAH, 2023)
This article tries to see the role of Indonesian diplomacy in resolving the South Thailand conflict. This article describes the efforts made by Indonesia to maintain security and stability in the Southeast Asian region. The Southern Thailand conflict has been going on for 14 years since 2004. This study used a qualitative method, collecting data using in-depth interviews with Sanusi and Hazmi, as Chairperson and Former Chairperson of the Indonesian Pattani Student Association. This long-running conflict has had many impacts on the people of Southern Thailand. Indonesia has several times been a facilitator in resolving the South Thailand conflict. In addition, various assistance from Indonesia through Nahdatul Ulama and Muhammadiyah, such as educational scholarships for children, building schools, or Islamic boarding schools, sent teachers to teach. The hope is that even though the conflict is not over, the children of Southern Thailand can still get their right to education, and the security stability of the Southeast Asian region will be maintained.